Improved multi-bits flipping algorithm for high-speed LDPC decoding - Ke-xiang MA; Ji-cheng SUN; Meng WANG; Yu-ming ZHANG; Hai-lin ZHANG (Tongxin xuebao)
In order to improve the decoding speed of the RRWBF algorithm, a multiple-bits selection mechanism was proposed to accelerate the decoding convergence speed of the RRWBF algorithm. However, the RRWBF algorithm with the multiple-bits selection mechanism will appear the bit-repeated flipping, which can impair the decoding performance of the RRWBF algorithm. Hence, a bit-repeated flipping elimination mechanism was proposed to reduce the bit-repeated flipping in the process of the multiple-bits flipping decoding. Simulation results show that the RRWBF algorithm with the multiple-bits selection and the repeated flipping elimination mechanism has a much faster decoding speed at the cost of a little decoding performance loss compared with the RRWBF algorithm.